1984
DOI: 10.1002/ana.410150119
|View full text |Cite
|
Sign up to set email alerts
|

Brain trace elements in Pick's disease

Abstract: The trace element content of the brain of two patients with Pick's disease examined postmortem was studied using instrumental neutron activation analysis. Results showed significant increases in chlorine, iron, manganese, sodium, and phosphorus and significant decreases in chromium, cesium, rubidium, and selenium and in the mean freeze-dried to wet-weight ratio for patients with Pick's disease compared with control patients. Brain zinc content was not elevated in the two patients, a finding that fails to suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0
5

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 2 publications
8
74
0
5
Order By: Relevance
“…Mercury accumulated in the cerebellum, thalamus, putamen, and in the upper parietal and occipital lobes of AD patients' brains [103]. Thompson and colleagues found significantly higher mercury levels in the amygdala, the nucleus basalis Meynert and non-significantly higher levels in the hippocampus of 14 AD patients compared with age-matched controls [104], while another study found significantly higher mercury levels in microsomes from AD brains [105].…”
Section: Mercury Exposure Accumulation and Excretion In Ad Patientsmentioning
confidence: 99%
“…Mercury accumulated in the cerebellum, thalamus, putamen, and in the upper parietal and occipital lobes of AD patients' brains [103]. Thompson and colleagues found significantly higher mercury levels in the amygdala, the nucleus basalis Meynert and non-significantly higher levels in the hippocampus of 14 AD patients compared with age-matched controls [104], while another study found significantly higher mercury levels in microsomes from AD brains [105].…”
Section: Mercury Exposure Accumulation and Excretion In Ad Patientsmentioning
confidence: 99%
“…The brain and nervous system are thought to be particularly vulnerable to oxidative stress due to limited antioxidant capacity, consumes 20 percent of the metabolic oxygen, neurons cannot synthesize glutathione and contains more of polyunsaturated fatty acids (Marksberry and Lovell 2007;. Elements receiving the most attention in Alzheimer disease are aluminum (Al), mercury (Hg), and iron (Fe) (Fraga et al 1990;Stacey and kappus 1982;Ehmann et al 1986). Of these, iron may have the most important pathophysiologic role as a catalyst for free radical generation by virtue of having a loosely bound electron and the ability to exist in more than one valence (Ehmann et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Elements receiving the most attention in Alzheimer disease are aluminum (Al), mercury (Hg), and iron (Fe) (Fraga et al 1990;Stacey and kappus 1982;Ehmann et al 1986). Of these, iron may have the most important pathophysiologic role as a catalyst for free radical generation by virtue of having a loosely bound electron and the ability to exist in more than one valence (Ehmann et al 1986). The mechanism by which iron can cause this deleterious effect is that Fe (II) can react with hydrogen peroxide (H 2 O 2 ) to produce the hydroxyl radical (OH . )…”
Section: Introductionmentioning
confidence: 99%
“…[15] Alzheimer hastalar›n›n beyin dokular›nda ortalama c›va düzeyinin 20-178 ng/g Hg aras›nda oldu¤u bildirilmifltir. [16] Multipl skleroz (MS) hastalar›n›n beyin omurilik s›v›s›nda (BOS) c›van›n normal hastalardan 7.5 kat fazla oldu¤u saptanm›flt›r. [17] Amalgam dolgular› ç›kar›lan ve ç›kar›lmayan MS hastalar› karfl›laflt›r›lm›fl; dolgular› ç›kar›lan grupta daha az depresyon, daha az sald›rganl›k ve daha az psikotik davran›fllar görülmüfltür.…”
Section: Discussionunclassified